Autorka i tłumaczka: dwie pełnoprawne postacie? O przekładzie feministycznym w Kanadzie na przykładzie Lettres d’une autre Lise Gauvin i „przekładu w rodzaju żeńskim” Susanne de Lotbinière-Harwood - Warmuzińska-Rogóż, Joanna (Przekłady Literatur Słowiańskich, 2018)
Author and Translator: Two Full-Fledged Characters? On the Feminist Translation in Canada Based on the Example of Lettres d’une autre by Lise Gauvin and “Feminine Translation” by Susanne de Lotbinière-Harwood Among many translation activities characteristic for Canada, a “feminine translation”, meaning an act of re-creation, is particularly worth mentioning. One of its representatives is Susanne de Lotbinière-Harwood, a translator of the texts of Quebec feminists, including Lise Gauvin’s Lettres d’une autre (1984) translated into English in 1989 (Letters from an Other). De Lotbinière-Harwood’s translation caused controversy, as — according to the critics — she explained to much to a reader, inserted too many footnotes and feminized the text more than the original. The translation activity of de Lotbnière-Harwood proves how, by using the creative approach to translation, the act of translation itself becomes visible, and the feminization of the target text creates a space for female expression also in a real world. KEY WORDS: feminist translation, Canada, Quebec, re-creation, Lise Gauvin